Paraneoplastic neuromyelitis optica spectrum disorder associated with ovarian dysgerminoma: a case report and literature review - Liu, Pan; Wang, Shuangying; Zhang, Chunhua; Li, Yanfang (Frontiers in Immunology, 2024)
Neuromyelitis optica spectrum disorder (NMOSD) is a clinical syndrome characterized by attacks of acute optic neuritis and transverse myelitis. We report a case with paraneoplastic NMOSD that improved after immunosuppressive therapy, surgical resection, and chemotherapy. A 48-year-old woman initially presented with gradual binocular visual loss over the course of one week. The patient was evaluated using magnetic resonance imaging (MRI), computed tomography (CT), visual evoked potential (VEP), pathological biopsy, immunohistochemistry, and autoimmune antibody testing. The brain MRI findings were normal. The VEP revealed prolonged P100 latencies in the right eye and an absence of significant waves in the left eye. Positive serum AQP4-IgG antibodies were found. The patient was diagnosed as NMOSD. Then the patient responded well to treatment with methylprednisolone. An ovarian tumor was found in the patient using abdominal MRI and CT. The tumor was surgically resected, and a pathological biopsy revealed that it was ovarian dysgerminoma. The patient received four rounds of chemotherapy after surgery. One month after the final chemotherapy treatment, a positron emission tomography (PET) scan revealed no tumor. The vision of the patient gradually recovered and serum AQP4 was negative. Furthermore, we summarized the characteristics of patients diagnosed with paraneoplastic NMOSD associated with ovarian neoplasms in previous studies. This is a characteristic case of overlapping NMOSD and ovarian dysgerminoma, demonstrating the importance of tumor therapy in cases of paraneoplastic NMOSD.